The predictive value The predictive value of the CONUT score combined with the A2DS2 scale for post-ischemic stroke infection - Zhang, Yongqing; Zhang, Wei; Zhou, Yiwu (Vojnosanitetski pregled, 2024)
Background/Aim. Stroke-associated infection is the most common and most serious complication of ischemic stroke (IS), which is the most important cause of death and disability in humans. The aim of the study was to determine the predictive value of nutrition risk score – Controlling Nutritional Status (CONUT) combined with Age, Atrial Fibrillation, Dysphagia, Sex, Stroke Severity (A2DS2) scale for post-IS infection (PISI) in IS patients. Methods. This retrospective study analyzed the clinical data of 333 IS patients admitted to the Emergency Department of West China Hospital of Sichuan University from December 2017 to April 2019. Patients were divided into the No-PISI group (244 cases) and the PISI group (89 cases) based on whether they had a PISI. Multivariate logistic regression analysis was used to identify independent risk factors for PISI. Receiver operating characteristic (ROC) curve analysis was used to evaluate the accuracy of different variables in predicting the outcome. Results. Multivariable logistic regression analysis showed that the CONUT score [odds ratio (OR) = 1.321, 95% confidence interval (CI): 1.040–1.677, p < 0.05] and age (OR = 1.026, 95%CI: 1.004–1.048, p < 0.05) were independent influencing factors for PISI. With the increase of the CONUT score, the proportion of PISI increased. Area under the ROC curve for predicting PISI was 0.651, 0.696, and 0.725 for CONUT, A2DS2, and CONUT plus A2DS2, respectively. Conclusion. Combining the CONUT score and A2DS2 scale enhances their predictability of PISI, thereby serving as a valuable tool for early risk assessment and clinical intervention.
Keywords: age factors; infections; nutritional status; prognosis; risk factors; stroke